2015
DOI: 10.1007/s12035-015-9233-z
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Carbon Nanostructures for Detection of Neurotransmitters

Abstract: Carbon-based materials, such as diamond-like carbon (DLC), carbon nanofibers (CNFs), and carbon nanotubes (CNTs), are inherently interesting for neurotransmitter detection due to their good biocompatibility, low cost and relatively simple synthesis. In this paper, we report on new carbon-hybrid materials, where either CNTs or CNFs are directly grown on top of tetrahedral amorphous carbon (ta-C). We show that these hybrid materials have electrochemical properties that not only combine the best characteristics o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
50
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(51 citation statements)
references
References 21 publications
1
50
0
Order By: Relevance
“…Microelectrodes of tungsten (W) wires with uniform layers SWCNT demonstrated outstanding performance and excellent stability/sensitivity towards some inorganic compounds and DA, epinephrine and serotonin (5‐HT) hydrochloride . The carbon hybrid material fully‐grown on top of the tetrahedral amorphous carbon (ta‐C) electrode by Sainio et al . was used for the electrocatalytic detection of AA and DA.…”
Section: Electrochemical Sensing Of Da By Using Cnt‐based Materialsmentioning
confidence: 99%
See 2 more Smart Citations
“…Microelectrodes of tungsten (W) wires with uniform layers SWCNT demonstrated outstanding performance and excellent stability/sensitivity towards some inorganic compounds and DA, epinephrine and serotonin (5‐HT) hydrochloride . The carbon hybrid material fully‐grown on top of the tetrahedral amorphous carbon (ta‐C) electrode by Sainio et al . was used for the electrocatalytic detection of AA and DA.…”
Section: Electrochemical Sensing Of Da By Using Cnt‐based Materialsmentioning
confidence: 99%
“…The activity of this electrode was found in the order MWCNT-T > MWCNT-COOH > MWCNT-OH > MWCNT-P. [60] Microelectrodes of tungsten (W) wires with uniform layers SWCNT demonstrated outstanding performance and excellent stability/sensitivity towards some inorganic compounds and DA, epinephrine and serotonin (5-HT) hydrochloride. [61] The carbon hybrid material fully-grown on top of the tetrahedral amorphous carbon (ta-C) electrode by Sainio et al [62] was used for the electrocatalytic detection of AA and DA. When the performance of ta-C/CNT electrode and bare ta-C electrode was compared, it was observed that bare electrode cannot resolve both analytes collectively; whereas ta-C/CNT was capable of differentiating these two analytes and LOD of 500 nM for DA was found (Figure 5a, b).…”
Section: Cnts Directly Deposited/grown On Electrodes or Functionalizementioning
confidence: 99%
See 1 more Smart Citation
“…When decorating the surface of carbon with metal, metal oxide/sulfide nanoparticles, the structure becomes catalytically active resulting in new types of catalyst beds suitable for all kinds of chemical reactors (Serp et al, 2003;Halonen et al, 2010). By exploiting the electrical conductivity, in conjunction with the already mentioned advantageous properties, we end up in electrodes for electrochemical sensing (Sainio et al, 2015), energy conversion , storage (Talapatra et al, 2006;Pushparaj et al, 2007), and harvesting (Aitola et al, 2011).…”
mentioning
confidence: 99%
“…The same group then directly grew carbon nanofibers (CNFs) on DLC thin film (Si substrate), which also exhibited wide water window. 85 Notably, the CNFs/DLC electrodes could detect glutamate without using any enzymes.…”
Section: Direct Growth Of Carbon Nanomaterials On Electrode Substratesmentioning
confidence: 99%